Implementasi Team Teaching dalam Pembelajaran Plain Language Taruna Air Traffic Controller di Politeknik Penerbangan Makassar - Ahmad Rossydi; Bellyndra Pudja; Ima Widiyanah; Maya Masita; Sari Agung Sucahyo (Politeknik Penerbangan Makassar, 2022)
Politeknik Penerbangan Makassar is a government academy under the Ministry of Transportation Indonesia with the principal task of implementing professional flight safety and engineering education programs. The objectives of this research were to: (1) describe the implementation of Team Teaching as a teaching method in plain language learning for air traffic controllers of Poltek Penerbangan Makassar students. (2) know whether or not the third-year students of Poltek Penerbangan Makassar are increasing their speaking skills. This research applied a quantitative method. The population of this research was year students of Poltek Penerbangan Makassar. There were two classes with 48 students, and the researcher divided into two groups, one class was the experimental group, and one more class was the control group. Each group consisted of 24 students. The data were collected using an observation checklist, a speaking duration table, and a questionnaire. This research proved that the team teaching method was adequate for plain language learning and increased the speaking skill of third-year cadets in Diploma III Air Traffic Control. Based on the average score in the pre-test and post-test that have been compared between the experimental group and control group. The score of the experimental group, which used the team teaching method in the treatment, showed 1,53% increase in score